Eficiência da adubação nitrogenada e manejo de resíduos na produção de sementes do capim-braquiária - Almeida, Gleice Menezes de (2015)
Plant residues removal (PRR) of cleaning cuts in seed crops of signalgrass (Brachiaria decumbens Stapf) can increase pure seed yield (PSY), but on the other hand, can reduce the plant nitrogen concentration (PNC), nitrogen (N) uptake, and affect the efficiency of N fertilization and the balance of N. There are still uncertainties, however, related to the interaction with no removal of plant residues (RNPR) of closing cleaning cuts and N fertilizer rates. This study conducted with signalgrass seed crops aimed to: i) evaluate the effects of plant residues management practices (PRMP) of cleaning cuts (plant residues removed or retained) in the initial october (in preparation for january harvest) and post-harvest january (in preparation for may harvest) and N fertilizer rates (0, 50, 100 and 150 kg ha-1) on PSY, in PNC, N uptake, and the balance presumed of N remaining after harvest (BPNRAH); ii) determine the nitrogen uptake efficiency (NUpE), nitrogen utilization efficiency (NUtE), nitrogen use efficiency (NUE), as well as other N efficiencies commonly used in the literature, and iii) determine if there was correlation between PNC, N uptake, NUpE, NUtE and NUE with PSY. The study was conducted in Umuarama, northwestern Paraná, Brazil, during the growing seasons of 2010-2011 and 2011-2012. The experiment was arranged in a randomized blocks design in a split-plot scheme, with three replications. The PNC and N uptake was significantly higher when plant residues were retained in the soil only in may 2011 harvest, but in other seed harvest these variables did not differ significantly in response to MPR evaluated. PNC and N uptake increased curvilinearly with increased N fertilizer rates in 2011 and 2012 harvests. In january and may harvests 2011 and may harvest 2012, PNC among N rates ranged from 0.9 to 1.3 g N kg dry matter-1 (DM), while N uptake ranged from 90 to 200 kg N ha-1. The results showed that in all harvests when the plant residues were removed the presumed balance of N remaining after harvest was curvilinear and negative. Conversely, when the plant residues were retained and the N fertilizer rate increased, this variable increased and then leveled. There were differences in the responses to N between harvest for NUpE, NUtE, NUE, nitrogen recovery efficiency (NRE) and nitrogen agronomic efficiency (NAgE). In general, NUpE and NUE from the 50 kg N ha-1 rate applied had better values. Physiologic N-efficiency (PNE) was affected by N fertilizer rate only on cycle of seed production of may 2012. Biomass plant efficiency (BPE) was not affected by N fertilizer rate in all harvest evaluated. Significant positive correlations, which were consistent in all seed harvest, were observed between the PNC, N uptake and NUtE with PSY, with exception of NUtE at May 2012 harvest, which the coefficient of correlation was not significant.